2012
DOI: 10.1111/j.1865-1682.2011.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Re-emerging Swine Viruses

Abstract: Summary In the past two decades or so, a number of viruses have emerged in the global swine population. Some, such as porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2), cause economically important diseases in pigs, whereas others such as porcine torque teno virus (TTV), now known as Torque teno sus virus (TTSuV), porcine bocavirus (PBoV) and related novel parvoviruses, porcine kobuvirus, porcine toroviruses (PToV) and porcine lymphotropic herpesviruses (PLHV), ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 190 publications
(286 reference statements)
1
78
0
Order By: Relevance
“…It has been associated with a number of porcine circovirus related diseases apart from PMWS, but it is also present in healthy herds [9]. In affected herds the rate of PCV2 infection is high but despite this only 5–30% of infected pigs develop clinical signs of PMWS [10]. The triggers to the onset of disease remains unclear but experimental settings in snatch farrowed colostrum deprived piglets have demonstrated that co-infections with PCV2 and for instance parvovirus or porcine reproductive and respiratory syndrome virus induce PMWS in contrast to infection with PCV2 alone [1113].…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with a number of porcine circovirus related diseases apart from PMWS, but it is also present in healthy herds [9]. In affected herds the rate of PCV2 infection is high but despite this only 5–30% of infected pigs develop clinical signs of PMWS [10]. The triggers to the onset of disease remains unclear but experimental settings in snatch farrowed colostrum deprived piglets have demonstrated that co-infections with PCV2 and for instance parvovirus or porcine reproductive and respiratory syndrome virus induce PMWS in contrast to infection with PCV2 alone [1113].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, a number of enteric viruses have emerged in the swine population, including porcine kobuvirus [17]. Kobuviruses are recently identified, nonenveloped, single-stranded, positive-sense RNA viruses in the family Picornaviridae [18-20].…”
mentioning
confidence: 99%
“…Within the genus Hepevirus, there exist at least four genotypes of HEV that infect humans. Genotypes 1 and 2 infect solely humans, whereas genotypes 3 and 4 are zoonotic, infecting humans and other animal species, such as swine (6,7).…”
mentioning
confidence: 99%